2014
DOI: 10.1519/jsc.0000000000000434
|View full text |Cite
|
Sign up to set email alerts
|

Strength Training Adaptations After Cold-Water Immersion

Abstract: Several studies analyzed the effectiveness of cold-water immersion (CWI) to support recovery after strenuous exercise, but the overall results seem to be conflicting. Most of these studies analyzed only short-term recovery effects, whereas the adaptational aspect has been widely neglected. Therefore, we analyzed the effects of repeated cooling after training sessions (CWI) on adaptations to strength training. Seventeen trained male students volunteered the study. After a 2-week familiarization period, a pretes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 28 publications
0
65
1
5
Order By: Relevance
“…Only two investigations have investigated the use of cold water immersion within a resistance training environment exceeding a 1 week period (see table 1.3), namely Yamane et al (2006) and more recently, Fröhlich et al (2014). Limitations exist regarding the practicality of the research designs in both these investigations.…”
Section: Cold Water Immersion and Responses Following Resistance Exermentioning
confidence: 99%
See 4 more Smart Citations
“…Only two investigations have investigated the use of cold water immersion within a resistance training environment exceeding a 1 week period (see table 1.3), namely Yamane et al (2006) and more recently, Fröhlich et al (2014). Limitations exist regarding the practicality of the research designs in both these investigations.…”
Section: Cold Water Immersion and Responses Following Resistance Exermentioning
confidence: 99%
“…Yamane et al (2006) used a resistance training protocol that only involved handgrip exercise, and also extrapolated performance results (1-RM) of this small muscle group to whole-body performance. Similarly, Fröhlich et al (2014) only trained the hamstring muscle group, and they only reported for changes in 1-RM and 12-RM strength. Despite these limitations, both studies concluded that regular cold water immersion attenuated training-induced adaptations.…”
Section: Cold Water Immersion and Responses Following Resistance Exermentioning
confidence: 99%
See 3 more Smart Citations